A STUDY TO EVALUATE THE TYPE AND CAUSE OF BLINDNESS/LOW VISION IN APPLICATIONS FOR BLINDNESS CERTIFICATE PRESENTING IN CHAMBA DISTRICT OF HIMACHAL PRADESH - SHARMA, SMRITI; NEGI, SHALOO; ADITYA KASHYAP (International Journal of Current Pharmaceutical Research, 2024)
Objective: This study aims to assess the prevalence, causes, and socio-economic impacts of visual impairment in the Chamba District of Himachal Pradesh, India. It seeks to identify the major factors contributing to visual disability and the role of literacy and employment status in influencing the lives of the visually impaired. Methods: A cross-sectional, hospital-based study was conducted over a period of one year, enrolling patients from the outpatient department of ophthalmology who were applying for visual disability certification. The study utilized a randomized sampling method and a semi-structured interview along with an examination form for data collection. Ethical approval was obtained, and the study adhered to ICMR and Helsinki Declaration guidelines. Participants underwent comprehensive ophthalmic evaluations, and data were analyzed using SPSS version 17.0. Results: Among the 270 participants evaluated, a higher prevalence of visual impairment was observed in males (n=149) compared to females (n=121), particularly within the age group of 21-40 y. The leading causes of visual disability included Corneal Opacity (16.25%), Retinitis Pigmentosa (15.83%), and Congenital Malformation (14.17%). Furthermore, literacy played a crucial role in employment opportunities, with 75.83% of the literate participants being employed, indicating a significant impact on the socio-economic status. Conclusion: The study highlights the multifaceted nature of visual impairment in the Chamba District, emphasizing the need for integrated public health strategies to address the identified challenges. Enhancing preventive measures, improving access to healthcare, and supporting rehabilitation services are essential steps towards mitigating the burden of visual impairment.